Does Parental Burnout Occur in Single Mother? Understanding Parental Burnout among Muslim Single Mother - Arini, Diana Putri; Pramudito, Anselmus Agung; Irene Prilia Bevi Utomo (Psikis : Jurnal Psikologi Islami, 2024)
Parental burnout is a condition of intense fatigue related to the role of being a parent, which impacts caregiving and increases the risk of maltreatment and child neglect. Previous research has shown that parenting stress is influenced by culture and religious beliefs. Therefore, this study aimed to explore parental burnout among Muslim single mothers. The study involved three participants, who were recruited through an open advertisement. The research used a qualitative approach with a phenomenological method. The results of the study revealed that all three participants experienced parental burnout in the form of exhaustion from their role as parents due to the dual burden of being both a mother and the primary breadwinner. The aspects of parental burnout they experienced were emotional exhaustion, a sense of contrast with their previous self, and a feeling of being fed up. However, emotional detachment was not found in any of the three participants. This study showed that single mothers experienced emotional exhaustion caused by their dual roles as caregivers and breadwinners. This condition affected their perspective on ideal parenting and lead to feelings of being fed up.